Externally tunable multichannel filtering applications of organic material based 1D magnetic cold-plasma photonic crystals. Issue 23 (17th May 2022) - Awasthi, S. K.; Aghajamali, Alireza; Mohamed, A. M.; Matar, Z. S.; Amin, A. F.; Aly, Arafa H.
Abstract : In the present research work, we employed the transfer matrix method (TMM) in addition to MATLAB software to examine the transmission properties of various organic-based one-dimensional (1D) magnetic cold-plasma photonic crystals (MCPPhCs). Abstract : In the present research work, we employed the transfer matrix method (TMM) in addition to MATLAB software to examine the transmission properties of various organic-based one-dimensional (1D) magnetic cold-plasma photonic crystals (MCPPhCs). The proposed structures were found to be made up of periodic layers of organic materials and magnetic cold-plasma (MCP) at normal incidence. An external magnetic field (B) polarized in right-hand (RH) and left-hand (LH) configurations was applied on 1D MCPPhCs. In this study, four organic materials, namely pentane, hexane, heptane, and octane, were chosen to design four 1D photonic crystals (PCs), named as PC1 (pentane-MCP), PC2 (hexane-MCP), PC3 (heptane-MCP), and PC4 (octane-MCP). Our results indicated that the central frequency of the resonant peaks of unit transmission inside the photonic band-gap (PBG) of the respective organic PCs could be tuned towards the higher or lower frequency side by applying B polarized in RH and LH configurations, respectively. We also studied the effect of the period number N to produce closely spaced N-1 transmission channels of unit transmission inside the PBG of all four organic PCs. By increasing the period number N we could increase the number of transmission channels inside the PBG as per our desire. These multiple resonant peaks of unit transmission inside PBG could be easily modulated inside the PBG to accommodate new frequencies by applying B polarized in either RH or LH configurations, respectively. Moreover, our results showed that under the RH configuration, increasing B resulted in a shifting of the resonant peak towards the higher frequency side with a reduction in its full width half maximum (FWHM), whereas the findings were the opposite in the case of increasing B under the LH configuration. These findings may be beneficial for designing externally tuneable organic chemical sensors in the microwave frequency region.